2023
DOI: 10.3389/fonc.2023.1095780
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus-infection related cryoglobulinemic vasculitis. Clinical manifestations and the effect of antiviral therapy: A review of the literature

Abstract: ObjectiveHepatitis B virus (HBV) infection causes chronic hepatitis, cirrhosis, and hepatocellular carcinoma. Furthermore, about 20% of the patients develop extrahepatic manifestations such as cryoglobulinemic vasculitis (CV), polyarteritis nodosa, non-rheumatoid arthritis, glomerulonephritis and non-Hodgkin lymphoma. This review analyzed literature data on clinical manifestations of HBV-related CV and the impact of antiviral therapy with analoques nucleotide.MethodsA PubMed search was performed to select elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…For patients with mild-to-moderate symptoms, treatment with antiviral therapy with NAs alone tended to be preferred. ( Mazzaro et al., 2023 , 2019 ) In our cohort, all patients ( n = 8) treated with NAs monotherapy had significantly improved clinical symptoms and viral suppression. Furthermore, one patient relapsed because of unauthorised withdrawal of antiviral therapy with NAs, which led to the return of her clinical symptoms, viremia and increased cryoglobulins.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For patients with mild-to-moderate symptoms, treatment with antiviral therapy with NAs alone tended to be preferred. ( Mazzaro et al., 2023 , 2019 ) In our cohort, all patients ( n = 8) treated with NAs monotherapy had significantly improved clinical symptoms and viral suppression. Furthermore, one patient relapsed because of unauthorised withdrawal of antiviral therapy with NAs, which led to the return of her clinical symptoms, viremia and increased cryoglobulins.…”
Section: Discussionmentioning
confidence: 67%
“…( Levo et al., 1977 ) The symptoms of HBV-related cryoglobulinemia patients vary from purpura and peripheral neuropathy to skin ulcer and glomerulonephritis. ( Mazzaro et al., 2023 ) Because of its rarity, there is a lack of definitive guidelines on treatment. Although China has the largest population of individuals with HBV infection, accounting for one-third of infected individuals in the world, ( Chen et al., 2018 ) there are still few studies focusing on HBV-related cryoglobulinemia.…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroids and plasma exchange can be co-administered to control severe cryoglobulinemic vasculitis flares; (4) B-cell depleting therapy with Rituximab (a chimeric monoclonal antibody to anti-CD20 antigen) to eliminate B lymphocytes that produce cryoglobulins. Several studies have demonstrated the effectiveness of Rituximab in treating cryoglobulinemia in patients who do not respond to the antiviral therapy alone; (5) anti-inflammatory drugs (NSAIDs) [ 10 , 13 , 14 , 15 ].…”
Section: Systemic Diseasesmentioning
confidence: 99%
“…In particular, 2%-5% of cases of mixed cryoV are attributable to hepatitis B virus (HBV) infection [5,36] . As viral suppression may induce remission of cryoV manifestations, antiviral therapy with nucleot(s)ide analogs such as entecavir or lamivudine is considered the mainstay treatment for HBV-related cryoV [10,[37][38][39][40][41][42][43] , while the addition of glucocorticoids and rituximab may be considered in patients with moderate to severe manifestations (recently reviewed in [41][42][43] ). An association of type II/III cryoglobulinemia and other viruses, for example, cytomegalovirus, Epstein-Barr virus, adenovirus, parvovirus B19, and human immunodeficiency virus, has also been suggested in previous studies [5,44,45] .…”
Section: Type Ii/iii (Mixed) Cryoglobulinemiamentioning
confidence: 99%